Uji In Silico Potensi Senyawa Aktif pada Daun Cempaka Putih (Magnolia Alba) Berbasis Molecular Docking Sebagai Antituberkulosis - Widhanti, Arin Arnaz; Darwinata, Agus Eka; Tarini, Ni Made Adi; Dwija, Ida Bagus Nyoman Putra (Riviera Publishing, 2025)
Resistance to Isoniazid (INH), primarily caused by mutations in the katG gene responsible for drug activation, remains a significant challenge in the treatment of tuberculosis (TB) and contributes to the global burden of drug-resistant TB. This challenge has stimulated the search for alternative therapeutic strategies, particularly the development of direct inhibitors of Enoyl-Acyl Carrier Protein Reductase (InhA), which can bypass the katG-dependent activation pathway. This study aimed to evaluate the potential of ten selected bioactive compounds derived from Magnolia alba (white champaca) leaves as direct InhA inhibitors using an in silico approach. Molecular docking analysis was performed to assess the binding affinity and interaction patterns of the selected compounds with the InhA protein, with Isoniazid used as a reference control. The results showed that among the ten compounds tested, Michelenolide exhibited the strongest binding affinity, with a docking score of ?9.1 kcal/mol. Although this value did not exceed the binding affinity of Isoniazid (?9.6 kcal/mol), Michelenolide demonstrated comparable interaction stability and a binding mechanism consistent with direct InhA inhibition. These findings suggest that Michelenolide holds promise as a lead compound for the development of novel anti-tuberculosis agents targeting INH-resistant Mycobacterium tuberculosis strains. Nevertheless, preliminary toxicity predictions indicate potential carcinogenic and mutagenic risks, highlighting the need for further structural optimization, in vitro validation, and pharmacological evaluation before clinical consideration.